NEUROENDOCRINE CARCINOMA: A CASE REPORT - Valencia, César (2015)
A rare case of neuroendocrine carcinoma of the cervix is reported. The symptoms reported in the initial consultation, the report of the pathological examination of the biopsy, the literature review and presents some relevant comments.